Komunikasi Pemasaran Terpadu: Implementasi Untuk UMKM - Joni Heruwanta; Ergo Nur patria Kurniawan; Enur Hotimah; Dede Nur Iskandar; Suhrowardi (LPPM STEBIS YPII, 2025)
Integrated marketing communications have been widely implemented in both large and small companies, including in the micro, small and medium enterprises (MSMEs) environment. MSMEs can use this program by adjusting it to the available budget. A simple program of integrated marketing communications that can be used is to introduce their products to customers by using brochures, banners, discounts or product samples (free), and online marketing, which can be used as a promotional tool with a low budget. MSMEs can carry out integrated marketing communications, although not optimally. Promotional activities carried out by MSMEs are still constrained by costs, the very minimal promotional capabilities are caused by the lack of funds so that only a few elements in integrated marketing communications can be implemented by MSMEs, namely: Advertising, publicity, sales promotions, and direct marketing.